Genetic Diversity and Population Structure of F3:6 Nebraska Winter Wheat Genotypes Using Genotyping-By-Sequencing - Eltaher, Shamseldeen; Sallam, Ahmed; Belamkar, Vikas; Emara, Hamdy A.; Nower, Ahmed A.; Salem, Khaled F. M.; Poland, Jesse; Baenziger, Peter S. (Frontiers in Genetics, 2018)
The availability of information on the genetic diversity and population structure in wheat (Triticum aestivum L.) breeding lines can help wheat breeders better use their genetic resources and manage genetic variation in their breeding program. The recent advances in sequencing technology provide the opportunity to create a large number of SNPs in large genome species (e.g. wheat). This large number of SNPs can be utilized for understanding genetic diversity and performing genome wide association studies for complex traits. In this study, we evaluated genetic diversity and population structure in a set of 230 genotypes (F3:6) from various crosses as a prerequisite for GWAS. Genotyping-by-sequencing provided 25,567 high-quality SNPs. The genetic diversity and polymorphism information content (PIC) values across chromosome varied from 0.09 to 0.37 with an average of 0.23 The distribution of markers on the chromosomes ranged from 319 loci in the chromosome 3D to 2370 loci in chromosome 3B. Three subpopulations were identified using structure software and confirmed by principal coordinate analysis. Analysis of Molecular Variance showed that 8% variance among populations and 92% within populations. Among the three sub-populations, population G2 exhibited the highest level of variability in all three genetic diversity indices: Shannon’s information index (I) = 0.494, diversity index (h) = 0.328 and unbiased diversity index (uh) = 0.331, whereas the sub-population G3 exhibited lowest level of variability (I = 0.348, h = 0.226 and uh= 0.236). The high genetic diversity found among genotypes can be used to develop new wheat cultivars with desirable characteristics.